Penerapan Konsep Tradisi “Baayun Mulud” sebagai Inspirasi Busana Pesta Malam - Nisa, Khairun; Suprihatin, Sri Emy Yuli (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2024)
Clothing is something that is closely related to humans today. Various types and forms of clothing are created to meet the trends and needs of society, one type of clothing that is growing the most is evening party clothing. This clothing has changed from year to year so that designers are required to be more creative and innovative in creating tonight's party clothing. The innovation that can be offered is by applying concepts that exist in Indonesian traditions as a source of inspiration in developing clothing. One tradition that can be a source of inspiration and concept in developing evening party clothing is the